Sulforaphane Protects Pancreatic Acinar Cell Injury by Modulating Nrf2-Mediated Oxidative Stress and NLRP3 Inflammatory Pathway. (26th October 2016) - Dong, Zhaojun; Shang, Haixiao; Chen, Yong Q.; Pan, Li-Long; Bhatia, Madhav; Sun, Jia
Abstract : Acute pancreatitis (AP) is characterized by early activation of intra-acinar proteases followed by acinar cell death and inflammation. Cellular oxidative stress is a key mechanism underlying these pathological events. Sulforaphane (SFN) is a natural organosulfur antioxidant with undescribed effects on AP. Here we investigated modulatory effects of SFN on cellular oxidation and inflammation in AP. AP was induced by cerulean hyperstimulation in BALB/c mice. Treatment group received a single dose of 5 mg/kg SFN for 3 consecutive days before AP. We found that SFN administration attenuated pancreatic injury as evidenced by serum amylase, pancreatic edema, and myeloperoxidase, as well as by histological examination. SFN administration reverted AP-associated dysregulation of oxidative stress markers including pancreatic malondialdehyde and redox enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx). In acinar cells, SFN treatment upregulated nuclear factor erythroid 2-related factor 2 (Nrf2) expression and Nrf2-regulated redox genes including quinoneoxidoreductase-1, heme oxidase-1, SOD1, and GPx1. In addition, SFN selectively suppressed cerulein-induced activation of the nucleotide-binding domain leucine-rich repeat containing family, pyrin domain-containing 3 (NLRP3) inflammasome, in parallel with reduced nuclear factor- (NF-) κ B activation and modulated NF- κ B-responsive cytokine expression. Together, our data suggested that SFN modulates Nrf2-mediated oxidative stress and NLRP3/NF- κ B inflammatory pathways in acinar cells, thereby protecting against AP.